Target, Suspect and Non-Target Screening of Silylated Derivatives of Polar Compounds Based on Single Ion Monitoring GC-MS - Gumbi, Bhekumuzi Prince; Moodley, Brenda; Birungi, Grace; Ndungu, Patrick Gathura (International journal of environmental research and public health, 2019)
Abstract: There is growing interest in determining the unidentified peaks within some sample spectra besides the analyses of interest. Availability of reference standards and hyphenated instruments has been a key and limiting factor in the rapid determination of emerging pollutants in the environment. In this work, polar compounds were silylated and analyzed with gas chromatography mass spectrometry (GC-MS) to determine the abundant fragments within the single ion monitoring (SIM) mode and methodology. Detection limits and recoveries of the compounds were established in river water, wastewater, bio-solid and sediment matrices. Then, specific types of polar compounds that are classified as emerging contaminants, pharmaceuticals and personal care products, in the environment were targeted in the Mgeni and Msunduzi Rivers. We also performed suspect and non-target analysis screening to identify several other polar compounds in these rivers. A total of 12 compounds were quantified out of approximately 50 detected emerging contaminants in the Mgeni and Msunduzi Rivers. This study is significant for Africa, where the studies of emerging contaminants are limited and not usually prioritized.
Keywords: Suspect and non-target analysis; GC-MS; Emerging pollutants; Pharmaceutical and personal care products